ANALISIS FILOSOFIS PENDIDIKAN ISLAM: PENGERTIAN, DASAR, DAN TUJUAN - Jaya; Aunia Afriani Lestari; Aulia Afriani Lestari; Farhan; Muhammad Almansyawwi; Muhammad Pran Yudisti (STKIP Subang, 2026)
Islamic education currently faces serious challenges in the form of value deconstruction due to globalization, secularization, and digital disruption, which trigger identity crises and moral degradation among the younger generation. This study aims to reconstruct the philosophical foundations of Islamic education to formulate an integrative paradigm relevant to contemporary challenges. Using a library research method with a descriptive-analytical approach, this research examines various authoritative literatures from both classical and contemporary figures, with a focus on up-to-date references (2018-2024). The results indicate that the reconstruction of Islamic education must be based on the integration of the trinity of concepts: Tarbiyah, Ta’lim, and Ta’dib, oriented toward Tawhidic values as a worldview. The main findings emphasize that the cultivation of adab (Ta’dib) is a crucial instrument for overcoming the dichotomy of knowledge and serves as a moral filter in the use of information technology. The study concludes that the ultimate vision of Islamic education is the achievement of the Insan Kamil (Perfect Human) status, which synergizes intellectual depth, steadfast faith, and noble character. The implications of this study demand a curriculum reorientation that is not only based on cognitive achievement but also on the internalization of transcendental values within a holistic educational ecosystem